VTMine for Visio: A Graphical Tool for Modeling in Process Mining - Shershakov, S. A. (Automatic control and computer sciences, 2021)
Process-aware information systems (PAISs) is a special class of information systems intended to support the tasks of initialization, end-to-end management, and completion of business processes. During their operation such systems accumulate a large amount of data that are stored in the form of event logs. Event logs are a valuable source of knowledge about the actual behavior of a system. For example, they include (i) information about the discrepancy between the real and prescribed behavior of the system, (ii) information for identifying the bottlenecks and performance issues, and (iii) information for detecting the antipatterns of building a business system. These problems are studied in the discipline called process mining. The practical application of the process mining methods and practices is carried out using specialized software for data analysts. The subject area of the process analysis involves the work of an analyst with a large number of graphical models. Such work can be more efficiently with a convenient graphical modeling tool. This paper discusses the principles of designing a graphical tool VTMine for Visio for process modeling, based on the widespread application Microsoft Visio for business intelligence. The features of the architecture design of the software extension for application in the process mining area are presented along with the features of integration with existing libraries and tools for working with data. The usage of the developed tool for solving various types of tasks in modeling and analysis of processes is demonstrated on a set of experimental schemes.